The Transformative Potential of AI in Education: Opportunities and Challenges - Butabayeva , Mukaddas (The Lingua Spectrum, 2025)
Artificial intelligence (AI) has transformed education by enhancing teaching methods, administrative efficiency, and accessibility. Through generative AI tools, adaptive learning systems, and real-time analytics, educators can personalize learning experiences and address challenges like inclusivity and resource distribution. AI also aids in automated grading and resource management, allowing teachers to focus more on mentorship. However, integrating AI presents ethical and practical challenges, such as data privacy concerns, algorithmic bias, and the risk of academic dishonesty. Despite these issues, the role of human educators is crucial, as AI cannot replicate empathy and cultural sensitivity. This article examines the potential of AI in education, considering its benefits, limitations, and ethical implications. By analyzing current literature and case studies, it highlights strategies to create an AI-enhanced educational system that prioritizes equity and holistic development. With careful planning, AI can foster innovative and inclusive learning environments.